Specific TLR-mediated HSP70 activation plays a potential role in host defense against the intestinal parasite Giardia duodenalis - Liu, Min; Yang, Yongwu; Zhu, Weining; Wu, Jingxue; Yu, Xiran; Li, Wei (Frontiers in Microbiology, 2023)
Giardia duodenalis, an important flagellated noninvasive protozoan parasite, infects the upper small intestine and causes a disease termed giardiasis globally. Few members of the heat shock protein (HSP) family have been shown to function as potential defenders against microbial pathogens, while such information is lacking for Giardia. Here we initially screened and indicated that in vitro Giardia challenge induced a marked early upregulation of HSP70 in intestinal epithelial cells (IECs). As noted previously, apoptotic resistance, nitric oxide (NO)-dependent cytostatic effect and parasite clearance, and epithelial barrier integrity represent effective anti-Giardia host defense mechanisms. We then explored the function of HSP70 in modulating apoptosis, NO release, and tight junction (TJ) protein levels in Giardia-IEC interactions. HSP70 inhibition by quercetin promoted Giardia-induced IEC apoptosis, viability decrease, NO release reduction, and ZO-1 and occludin downregulation, while the agonist celastrol could reverse these Giardia-evoked effects. The results demonstrated that HSP70 played a previously unrecognized and important role in regulating anti-Giardia host defense via attenuating apoptosis, promoting cell survival, and maintaining NO and TJ levels. Owing to the significance of apoptotic resistance among those defense-related factors mentioned earlier, we then elucidated the anti-apoptotic mechanism of HSP70. It was evident that HSP70 could negatively regulate apoptosis in an intrinsic way via direct inhibition of Apaf-1 or ROS-Bax/Bcl-2-Apaf-1 axis, and in an extrinsic way via cIAP2-mediated inhibition of RIP1 activity. Most importantly, it was confirmed that HSP70 exerted its host defense function by downregulating apoptosis via Toll-like receptor 4 (TLR4) activation, upregulating NO release via TLR4/TLR2 activation, and upregulating TJ protein expression via TLR2 activation. HSP70 represented a checkpoint regulator providing the crucial link between specific TLR activation and anti-Giardia host defense responses. Strikingly, independent of the checkpoint role of HSP70, TLR4 activation was proven to downregulate TJ protein expression, and TLR2 activation to accelerate apoptosis. Altogether, this study identified HSP70 as a potentially vital defender against Giardia, and revealed its correlation with specific TLR activation. The clinical importance of HSP70 has been extensively demonstrated, while its role as an effective therapeutic target in human giardiasis remains elusive and thus needs to be further clarified.